Pengaruh Ukuran Perusahaan, Likuiditas, Dan Corporate Social Responsibility Terhadap Kinerja Keuangan (Studi Perusaan Manufaktur Di Bursa Efek Indonesia Tahun 2020-2022) - Ardia Pramesti Regita; Sri Sudarsi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine and examine the effect of company size, liquidity, and corporate social responsibility on financial performance. This study uses secondary data in the form of annual reports and financial statements of companies obtained from the indonesian Stock Exchange (IDX) website by taking samples used in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The type of data used in this study using panel data. Sampling technique using a proposed sampling, companies that meet the criteria in this study as many as 30 companies. Data analysis techniques used in this study is to use multiple regression analysis using SPSS software version 25 to test the effect of the independent variable on the dependent variable. The results showed that the variable size of the company (total assets), liquidity (CR) has a positive and significant effect on financial performance, while the variable corporate social responsibility (CSRIndeks) has a negative effect on financial performance (ROA). Keywords: company size (total assets), liquidity (CR), corporate social responsibility (CSRIndex), financial performance (ROA).